ANALYSIS OF SAW WELDING PROCESS IN PRESSURE VESSEL TANK FOR AMMONIA FLUID WITH PRESSURE CAPACITY OF 13 Pa - Aa Santosa Santosa; Oleh Oleh; Bayu Nugroho Putra Santoso (Universitas Majalengka, 2022)
Pressure vessels are widely used to accommodate pressurized fluids, one of which is to accommodate ammonia with a working pressure of 13 Pa. Pressure vessels use ASTM A516 Grade 70 as raw material. This material has the advantage of being resistant to changes in temperature and good weldability. To make this equipment, a lot of joining processes are used, because the welding process is unavoidable in the construction of joints and the manufacture of processing equipment made of stainless steel. Of the many metal materials, ASTM A516 Gr 70 because of its low carbon content thereby avoiding the possibility of sensitization of the welded components, has good weldability properties because it has high temperature resistance. There are many ways of connecting with welding techniques, one of which is using the Submerged Arc Welding (SAW) technique. (SAW) is a welding process using a submerged arc in flux. The function of the flux is to prevent oxidation, as an alloying element in the chemical composition of the weld metal, as a stabilizer, and as an oxidizer. The welding carried out in this study uses current variations, including 350 A. , 400 A, 410 A san 430 A . Next, a test is carried out from the results of the welding process such as a tensile test tap test. From the test results, it is obtained that the current strength value is suitable to be recommended for the welding process, namely at a current of 400 A seen from the value of the tensile test results and the hardness test. Keywords : Pressure vessel, ASTM A516 Gr 70, SAW welding